Comparison of User Experience and Satisfaction in Digital Payment Applications Using the PSSUQ and EUCS Methods (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The rapid adoption of digital wallets such as DANA and GoPay has not yet been matched by comprehensive evaluations of user experience and satisfaction. National survey data indicates that GoPay is currently Indonesia's most widely used digital payment application. This study aims to compare the two most popular digital payment apps, DANA and GoPay, using the Post-Study System Usability Questionnaire (PSSUQ) and End-User Computing Satisfaction (EUCS) methods. A total of 136 respondents (68 users for each application), aged 18–40 and residing in Bali Province, were surveyed. Additionally, 2,366 user reviews from the Google Play Store were analysed using the Random Forest algorithm for sentiment classification. The results reveal that GoPay outperforms DANA in terms of usability (PSSUQ score of 2.04) and user satisfaction (EUCS average score of 4.34), compared to DANA (2.32 and 3.33, respectively). Information quality emerged as the most influential factor affecting user satisfaction, with Spearman correlation scores of 0.949 for DANA and 0.948 for GoPay. This study offers practical insights for developers and users to better understand and improve the digital payment user experience. However, the research is limited by the sample size of user reviews and the regional scope of respondents.